2017
DOI: 10.9734/arrb/2017/33477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of New Delhi Metallo Beta Lactamase 1 (NDM-1) Producing Bacterial Isolates in Kano- Northwestern Nigeria

Abstract: New Delhi Metallo Beta Lactamase 1 (NDM-1) is an enzyme with zinc ions at its active site that cleaves the amide bond of β-lactam ring and provides resistance against major classes of βlactam antibiotics. The molecular detection of NDM-1 producing bacterial isolates from tertiary Hospitals in Kano was investigated. A total of 500 bacterial isolates of Enterobacteriaceae and Pseudomonas aeruginosa from samples of blood, urine, catheter tip were screened for NDM-1 over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…The prevalence of MBL-producing Gram-negative bacteria in this study was found to be 39.3%. This result is higher than that reported by Oduyebo et al (2016) in Lagos (8.5%) and Abdullahi et al (2017) in Kano (8.6%). The highest MBL producers were Escherichia coli, Burkholderia cepacia, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia fonticola and Proteus mirabilis.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The prevalence of MBL-producing Gram-negative bacteria in this study was found to be 39.3%. This result is higher than that reported by Oduyebo et al (2016) in Lagos (8.5%) and Abdullahi et al (2017) in Kano (8.6%). The highest MBL producers were Escherichia coli, Burkholderia cepacia, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia fonticola and Proteus mirabilis.…”
Section: Discussioncontrasting
confidence: 70%
“…Metallo beta-lactamase-producing Gram-negative bacteria have been reported as important cause of nosocomial and community-acquired infections including urinary tract infections (UTIs), surgical wound infections, pyogenic infections, cystic fibrosis, septicemia, pneumonia, meningitis, bacteremia, endocarditis, osteomyelitis, pyelonephritis, enterocolotis, puerperal sepsis, peritonitis and soft tissue infection among others (Samuel et al, 2010;Chollom et al, 2012). The prevalence rates of these infections have been reported within and outside the country by many researchers: 11.23% by Ajuba et al (2020) in Anambra, 8.5% by Oduyebo et al (2016) in Lagos, 8.6% by Abdullahi et al (2017) in Kano and 36.1% by Adam and Elhag (2018) in Sudan. Thus, early detection of MBL producing organisms is of great importance to mitigate easy dissemination of infectious resistant phenotypes and also for prompt implementation of effective therapeutic control measures.…”
Section: Introductionmentioning
confidence: 99%
“…Carbapem-resistant bacteria such Escherichia coli and Klebsiella pneumoniae are mostly endemic in specific geographical regions, but reports of their spread into other geographical locations are point of grave concern these days. In Nigeria there have been reports of carbapenemase producing clinical isolates of enteric bacteria particularly among E. coli and Klebsiella species [1,15,16]. These strains become a serious threat to public health, associated with high mortality rates and have the potential to spread widely.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] in South Africa, Kenya, Ethiopia and other eastern/southern African countries. In Nigeria, NDM-1 has been reported amongst Gram-negative enteric bacteria in various geopolitical zone, including the Southwestern region (Lagos), Northeastern region (Maiduguri), South-southern region (Bayelsa), North-western region (Kano), and South-eastern region (Enugu) of the country [22][23][24][25][26][27][28][29] however, non has reported NDM-1 amongst Gram-positive strains.…”
Section: Introductionmentioning
confidence: 99%